Establishment of a set of St-group wheat-Thinopyrum ponticum derivative lines conferring resistance to powdery mildew - Cheng, Xiaofang; Guan, Yue; Zhao, Jianing; Yang, Xiaoying; Wang, Guangyi; Li, Tingdong; Deng, Pingchuan; Chen, Chunhuan; Zhao, Jixin; Wang, Changyou; Liu, Xinlun; Ji, Wanquan (Frontiers in Plant Science, 2025)
Thinopyrum ponticum (2n = 10x = 70, EeEeEbEbExExStStStSt), a wild relative of common wheat (Triticum aestivum L., 2n = 6x = 42), possesses extensive genetic diversity. The primary objective of this study was to develop and evaluate alien derivatives carrying the St-chromosome from Th. ponticum, aiming to improve wheat disease resistance and agronomic traits. In this study, a set of St-chromosome alien derivatives was developed from Th. ponticum. Chromosomal compositions, karyotypes and homoeologous group affiliations of seven derivatives were characterized using genomic in situ hybridization (GISH), fluorescence in situ hybridization (FISH), multicolor GISH (mc-GISH), and liquid chip analysis. Resistance assessments showed that the 4St and 7St derivatives exhibited strong resistance to the E09 isolate at the seedling stage and to naturally occurring pathogen mixtures in the field at the heading stage. The 7St derivative line, based on agronomic trait evaluations, is considered an ideal bridging material for breeding, with a reduction in plant height to 71.3 cm, while thousand-kernel weight and kernel length increased to 41 g and 0.77 cm, respectively. Specific markers for the St-homoeologous groups were developed through genome sequencing, achieving a development efficiency of 47.5%. This study provides a theoretical and technical basis for applying Th. ponticum genetic resources to improve wheat resistance and agronomic performance.